Oxidative catalytic valorization of industrial lignin into phenolics: Effect of reaction parameters and metal oxides. (May 2022) - Kumar, Avnish; Biswas, Bijoy; Kaur, Ramandeep; Rawat, Shivam; Krishna, Bhavya B.; Kumbhar, Pramod; Pal, Siddhartha; Padmanabhan, Sasisankar; Bhaskar, Thallada
Graphical abstract: Highlights: Depolymerisation of an industrial by-product lignin in atmospheric air and O2 . Maximum bio-oil (49 wt%) was observed with Co/CeO2 in 10 bar O2 . Maximum (78 area%) selectivity towards acetosyringone with Co/CeO2 in air. Co/CeO2 exhibited good performance up to four successive cycles. 1 H NMR, FT-IR and Py-GC/MS analysis revealed macromolecular breakdown of lignin. Abstract: Oxidative depolymerization of an industrial lignin was performed to study the effect of various metal oxides in oxygen and air atmosphere. CeO2 exhibited excellent catalytic property, and promoted the production of bio-oil yield up to a maximum of 49 wt% in 10 bar O2, whereas 31 wt% bio-oil was noticed in atmospheric air. GC–MS analysis of bio-oil showed that high selectivity towards acetosyringone was observed in the presence of air (70.5 area%) as compared to oxygen (48.1 area%). Herein, we have also applied transitional metals (Co, Mn and Cu) doped CeO2 catalysts. Compared to Cu and Mn, Co metal showed efficient activity that promoted the breaking of labile β-O-4 linkages via the conversion of Cα -OH in to carbonyl group in atmospheric air resulting in the formation of acetosyringone up to 78 area%. Moreover, it exhibited excellent catalytic activity up to four successive cycles. Catalyst has been characterized by XRD, BET, TEM, FT-IR and Raman spectroscopy.